Inference, arbitrage, and asset price volatility - Tobias Adrian (Federal Reserve Bank of New York, 2004)
Does the presence of arbitrageurs decrease equilibrium asset price volatility? I study an economy with arbitrageurs, informed investors, and noise traders. Arbitrageurs face a trade-off between arbitrage and inference: they would like to buy assets in response to temporary price declines (the arbitrage effect) but sell when prices decline permanently (the inference effect). In equilibrium, the presence of arbitrageurs increases volatility when the inference effect dominates the arbitrage effect. From a technical point of view, this paper offers closed-form solutions to a dynamic equilibrium model with asymmetric information and non-Gaussian priors.
Keywords: G10; G12; G14; 330; asset pricing; learning; asymmetric information; limits to arbitrage; Börsenkurs; Volatilität; Arbitragegeschäft